TWO NOVEL FLAVONE C-GLYCOSIDES ISOLATED FROM AFROCARPUS GRACILIOR: POM ANALYSES AND IN VITRO CYTOTOXIC ACTIVITY AGANIST HEPATOCELLULAR CARCINOMA - Kamal, Amel M.; Abdelhady, Mohamed; Ben Hadda, Taibi (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: Cancer is considered as one of the top reasons of death and the number of cases increasing gradually. Cancer is severe clinical difficulty to the health caution system. This study explored two novel polyphenols of Afrocarpus gracilior Pilger growing in Egypt and evaluated their cytotoxic activity. Methods: Methanolic (80%) extract of the leaves of A. gracilior was subjected to column chromatography; the chemical structures of the isolated compounds were established by advanced spectral techniques: UV, 1H, 13C NMR, two dimensional NMR (2D NMR) and electron spray ionization mass spectroscopy (ESI-MS). Compounds 1 and 2 were studied for their cytotoxic activity against hepatocellular carcinoma (Hep-G2) using sulforhodamine B (SRB) assay. Furthermore the pharmacokinetics profiles of these molecules were accessed by employing Petra/Osiris/Molinspiration (POM) analyses. Results: Two novel C-flavonoid glycosides were isolated [1: Apigenin 8-C-β-D-glucopyranosyl-(1```→4``)-O-β-D-glucopyranoside] and [2: 7-O methyl-luteolin 8-C-β-glucopyranosyl-(1```→4``)-O-β-D-glucopyranoside]. They exhibited significant cytotoxic activity (IC50 = 9.02 and 15.61 µg/ml, respectively) against Hep-G2 cells. The POM analyses revealed that the activity of these two compounds depends on the presence of glucosyl and alkyl groups at the internal and terminal atmosphere of the compounds. Conclusion: These findings demonstrated that the leaves of A. gracilior contain a series of bioactive polyphenolic compounds with significant cytotoxic properties against hepatocellular carcinoma and may be used as alternative anticancer agents for doxorubicin. On the basis of POM calculations, it will be interesting to develop some alternative flavones because the deglucosylated derivatives have a better drug score than parent molecules. This preliminary study will be extended to other strains of cancer.